2019
DOI: 10.1177/1753193419871671
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and long-term outcomes for hand and wrist pyrocarbon implants

Abstract: The article reviews the techniques and surgical outcomes of arthroplasties of the metacarpophalangeal, carpometacarpal and the wrist joints. In my patients, interposition pyrocarbon implants quickly achieve functional recovery and do not deteriorate time. Bony and articular tolerances are remarkable. These implants are a valid alternative to conventional arthroplasties, such as trapeziectomies, silicone implants and total joint replacements. Because of the implant’s small size, the surgery can be done through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…Interposition implants such as silicone, pyrocarbone, autologous, allografts and synthetic materials combined with distal pole excision might be an option for the treatment of a primary degenerative ST joint in absence of DISI. In our case these options should be avoided as they have already failed, and would increase further carpal instability (Bellemère, 2019; Garcia‐Elias, 2011; Pequignot et al, 2005). As significant bone loss and scaphoid height were already present, further debridement would not be an option as literature demonstrates that scaphoid height loss of over 3 mm leads to further carpal instability (Obert et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Interposition implants such as silicone, pyrocarbone, autologous, allografts and synthetic materials combined with distal pole excision might be an option for the treatment of a primary degenerative ST joint in absence of DISI. In our case these options should be avoided as they have already failed, and would increase further carpal instability (Bellemère, 2019; Garcia‐Elias, 2011; Pequignot et al, 2005). As significant bone loss and scaphoid height were already present, further debridement would not be an option as literature demonstrates that scaphoid height loss of over 3 mm leads to further carpal instability (Obert et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Our review of all pyrocarbon interposition arthroplasty of the wrist and hand also found stable outcomes over time in the medium and long terms. 36 Another alternative for the treatment of advanced stages of wrist destruction is proximal row carpectomy with a resurfacing capitate pyrocarbon implant (RCPI). Most studies [37][38][39][40] reported very few cases with a limited follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrocarbon implants are being increasingly used in the hand and wrist, particularly for carpal arthritis. 30 The biomechanical properties of pyrocarbon make it ideal for small joint arthroplasty in the hand and wrist. 31 With a similar modulus of elasticity to bone, excellent wear characteristics and good biocompatibility with bone and cartilage pyrocarbon implants are ideal to use when situating adjacent to Outcomes from the RCPI have demonstrate a flexionextension arc range of 55 to 82 with a grip strength range of 16 to 38 across six studies.…”
Section: Capitate Resurfacingmentioning
confidence: 99%